Information Literacy Training in Teaching Ethical and Plagiarism-Avoidance Skills among First-Year Students at a Private Tertiary Institution - Khoza, Banele Witness; Wessels, Nicoline (Mousaion: South African Journal of Information Studies, 2023)
There is an expectation that students in higher education be in possession of certain information or research skills. Information literacy equips students with skills to ethically handle and use information, thereby respecting the ideas of others. First-year students at the private higher education institution under discussion lack information literacy skills necessary to handle unethical use of information in their academic activities, despite information literacy sessions being available to them. The problem seems to be less a wilful disregard for the rules than compounded by inexperience and a lack of in-depth understanding of the application of information literacy skills. This article reports on the findings of a master’s study undertaken to investigate the role the information literacy training offered at the institution plays in inculcating ethical use of information skills and plagiarism-avoidance techniques among first-year students. The study adopted a qualitative approach using questionnaires and interviews where 188 first-year students were purposively selected through a census. The findings revealed that information literacy plays a significant role in raising awareness of ethical use of information issues and plagiarism. It trains students in the efficient and effective access and use of sources and sensitises them concerning upholding academic integrity. Although the training has been effective in sensitising students about the importance of academic integrity, it has, however, not been effective in curbing plagiarism as cases of plagiarism are still high. The study recommends the development of a formal information literacy programme that will teach plagiarism-avoidance techniques and impart and instil ethical use of information skills.